Answer:
The top choice is the answer. a1=7; an= 3*a_(n-1)
Explanation:
Begin by finding out what the terms are multiplied by. It is a geometric sequence so multiplication is involved.
Take the 3rd term (63) and divide it by the second term.
63/21 = 3
What this means is that each term in the sequence is multiplied by 3 to get to the next term.
The first term is 7
So the answer is an = 3* a_n-1
The answer must be the top one. See if it works.
a2 = 3*a_(2 -1 )
a2 = 3 * a1
a2 = 3 * 7
a2 = 21 which it does.